Livestock and water: understanding the context based on the 'Comprehensive Assessment of Water Management in Agriculture.' - Bossio, Deborah A. (Commonwealth Scientific and Industrial Research Organisation, 2009)
The recently completed 'Comprehensive Assessment of Water Management in Agriculture' (CA) assessed the benefits, costs and impacts of the past 50 years of water development. It highlighted important trends that frame the challenges in water resources management of today and into the future, and critically evaluated solutions that people have developed to cope with these challenges. Important past trends include increases in food production that have outpaced population growth, much of this due to a doubling of the global irrigated area between 1961 and 2003, and accompanying declines in the health of aquatic ecosystems resulting from demands for, and impacts of, water use in agriculture. The future will bring new pressures on water resources and ecosystems as demands from sectors other than agriculture increase (including water for biofuel production), populations rise and become more wealthy, which leads to demand for foods that are more water intensive to produce, and climate change increases uncertainty and risk in our agricultural systems. Modelling predictions and analysis of scenarios show that water demand may rise from between only 20 up to 90% over the next 50 years, depending on how we choose to manage water in agricultural systems in the future. Owing to the importance of meat in changing diets and the role of livestock in managing land degradation, livestock is central to many of the issues that will determine whether or not optimistic scenarios (minimised increased demand for agricultural water in the future) can be achieved. This paper briefly summarises the insights and results of the CA, and highlights the areas where livestock management is most closely related to major water challenges and global recommendations of the CA. The purpose of this introductory paper is to set the context within which the importance of enhancing livestock water productivity in mixed farming systems can be appreciated.